2005
DOI: 10.1016/j.ijgo.2005.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasound assessment and serum cancer antigen 125 in the diagnosis of ovarian tumors

Abstract: Sonographic evaluation with predefined specific criteria for the detection of a solid tumor component is an accurate method of preoperative discrimination between benign and malignant ovarian tumors. A serum CA 125 assay may assist in eliminating false-positive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Power Doppler (PD) imaging could depict more color flow features with vascular perfusion superimposed on B‐mode sonography compared with conventional color Doppler 29,30 . This method was applied to differentiate benign from malignant adnexal masses, and the results are shown in Table 4 31–35 . PD imaging increased the specificity of other diagnostic modalities, especially B‐mode sonography 31–34 .…”
Section: Conventional 2d Ultrasoundmentioning
confidence: 99%
See 3 more Smart Citations
“…Power Doppler (PD) imaging could depict more color flow features with vascular perfusion superimposed on B‐mode sonography compared with conventional color Doppler 29,30 . This method was applied to differentiate benign from malignant adnexal masses, and the results are shown in Table 4 31–35 . PD imaging increased the specificity of other diagnostic modalities, especially B‐mode sonography 31–34 .…”
Section: Conventional 2d Ultrasoundmentioning
confidence: 99%
“…Several studies have been reported involving the use of contrast agents in the differentiation of benign and malignant adnexal masses 36–41 . The reports employing color Doppler sonography demonstrated a significant difference in the enhancement patterns between benign and malignant adnexal masses, and the potential of sonographic contrast agents to identify the tumor vascularity 33–35 . However, Flesicher et al 39–41 .…”
Section: Conventional 2d Ultrasoundmentioning
confidence: 99%
See 2 more Smart Citations
“…Afin d'améliorer ces performances des index de risque de malignité ont été proposés [28][29][30][31][32][33][34][35][36]. Le calcul de ces index associe dans des algorithmes l'état ménopausique, les caractéristiques échographiques et la valeur du CA 125.…”
Section: Ca 125 En Situation Diagnostiqueunclassified